Redukce radiační zátěže užitím fluoroskopické navigace při transpedikulární instrumentaci - Hart, R; Komzák, M; Bárta, R; Okál, F; Srůtková, E (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2011)
PURPOSE OF THE STUDY: The variability in width, height, and orientation of spinal pedicles makes pedicle screw insertion a delicate operation. Fluoroscopic guidance often exposes the patient and especially surgeons to relatively high doses of ionising radiation. The use of pulsed fluoroscopy is safer, as compared to continuous fluoroscopy, because of reduced radiation exposure. There are increasing numbers of literature reports regarding the high doses of radiation to which orthopaedic and spine surgeons are exposed during surgical procedures. Spine surgery can be associated with significant radiation exposure to the surgical staff. The purpose of this prospective study was to compare a computer-assisted navigation with a conventional procedure in order to assess if it is possible to reduce radiation exposure while preserving the accuracy of screw placement. MATERIAL AND METHODS: The first "conventional" group consisted of 30 patients, with an average of 1.9 segments of the lumbar spine stabilised. Screws were inserted transpedicularly under image intensifier guidance. In the second "navigated" group of 30 patients, stabilisation of 1,8 segments was performed on average. A CT-free fluoroscopic 2D spinal navigation system (VectorVision, Brain LAB, Germany) was used intra-operatively. It combines image-guided surgery with C-arm fluoroscopy. For each surgery (navigated or not), the duration of irradiation was recorded. The irradiation duration was collected from the X-ray image intensifier. In both groups the screw positioning accuracy was controlled intra-operatively according to Learch's, Acikbas's, and Whitecloud's methods from AP and lateral images and by meticulous pedicle palpation. RESULTS: The irradiation duration calculated to one vertebra (two screws) was significantly shorter in the second (navigated) group (3.4 s) than in the first (conventional) group (14.4 s). The mean duration of data registration was 6.0 minutes (range, 3 to 11 minutes). The mean ratio according to Acikbas's calculation method was 43.2 % (range, 32 % to 74 %) in the first (conventional) group and 44.1 % (range, 35 % to 76 %) in the second (navigated) group. DISCUSSION: During a conventional surgical procedure many X-ray images are made to control the accuracy of screw insertion. If the trajectory is not satisfying, it must be corrected or the pedicle is drilled again, always with a new fluoroscopic control. The process is repeated until satisfactory orientation is achieved. This is the explanation for a much longer duration of irradiation in conventional procedures. Navigation facilitates the surgical act, enabling us to acquire the right position of all screws, with only an AP image and a lateral image at the beginning of instrumentation for data registration; prolongation of the operative time is irrelevant. CONCLUSIONS: Navigation allows us to keep the same accuracy of pedicle screw placement while reducing radiation exposure of the surgeons and operating room staff by about one quarter. In multiple-level vertebral instrumentations this reduction is more pronounced. In centres where many procedures involving spine instrumentation are done every day, the "saved" exposure time can amount to hours.
Keywords: dospělí; Surgery, Computer-Assisted; Female; fluoroskopie; Adult; ženské pohlaví; kostní šrouby; lidé; bederní obratle; Fluoroscopy; Thoracic Vertebrae; Male; Aged; Lumbar Vertebrae; hrudní obratle; intervenční radiografie; lidé středního věku; senioři; mužské pohlaví; Radiation Dosage; chirurgie s pomocí počítače; dávka záření; Middle Aged; Radiography, Interventional; Bone Screws; Humans